Intimacy as related to cortisol reactivity and recovery in couples undergoing psychosocial stress - Ditzen, Beate (Psychosomatic medicine, 2019)
Objective The importance of recovery from stress is evident in times of high prevalence of stress-related diseases. Intimacy has been found to buffer psychobiological stress reactivity, suggesting that emotional and physical closeness might trigger biological mechanisms that underlie the health-beneficial effects of couple relationships. Here, we investigated whether couples' spontaneous expression of intimacy before and after psychosocial stress exposure in the laboratory reduced cortisol reactivity and accelerated recovery. - Methods Data from 183 couples (366 individuals) were analyzed. Couples were randomly assigned to one of the following three experimental conditions: only the female partner (n = 62), only the male partner (n = 61), or both partners were stressed in parallel (n = 60) with the Trier Social Stress Test. Couples' behavior was videotaped and coded for expressions of intimacy, and saliva samples were taken repeatedly (nine times) to analyze cortisol levels before and after stress. Data were analyzed using hierarchical linear modeling. - Results Observed partner intimacy reduced cortisol responses to stress in women (B = −0.016, SE = 0.006, p = .008), although this effect was eliminated among women using oral contraceptives. Observed partner intimacy also reliably accelerated cortisol recovery in men (B = −0.002, SE = 0.001, p = .023) and women (B = −0.002, SE = 0.001, p = .016). - Conclusions Spontaneous nonverbal expressions of intimacy seem to regulate the effects of acute environmental demands on established biological indices of stress response.
revision received June 29, 2018
Gesehen am 26.07.2019